Stochastic linearization of nonlinear point dissipative systems - James A. Reneke (International Journal of Mathematics and Mathematical Sciences)
Stochastic linearization produces a linear system with the same covariance kernel as the original nonlinear system. The method passes from factorization of finite-dimensional covariance kernels through convergence results to the final input/output operator representation of the linear system.